Generalized granuloma annulare coexisting with metastatic carcinoma of unknown origin (CUP syndrome) – a case report - Bacharewicz-Szczerbicka, Joanna; Reduta, Teresa; Kiluk, Paulina; Andrzejewska, Anna; Flisiak, Iwona (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction. Generalized granuloma annulare (GGA) is characterized by a chronic course and a poor response to treatment. So far cases of GGA coexisting with diabetes, hyperlipidemia, thyroid diseases and malignant neoplasms have been described. Objective. To present a case of generalized granuloma annulare coexisting with metastatic carcinoma of unknown primary localization. Case report. A 58-year-old patient was diagnosed with metastases to lymph nodes of squamous cell carcinoma of unknown primary localization in June 2014. The patient was admitted in November 2014 due to skin lesions lasting since April 2014. On examination, disseminated, red papules with annular distribution on the neck, trunk and upper limbs were noticed. The lymph nodes were enlarged. The histopathological examination of papular lesions revealed granuloma annulare. After skin biopsy the flattening of those lesions was observed. Conclusions . The presented case indicates the need of diagnostic examinations for cancer in patients with GGA.